Repo runs - Antoine Martin; David Skeie; Ernst-Ludwig von Thadden (Federal Reserve Bank of New York, 2010)
This paper develops a model of financial institutions that borrow short-term and invest in long-term marketable assets. Because these financial intermediaries perform maturity transformation, they are subject to runs. We endogenize the profits of an intermediary and derive distinct liquidity and solvency conditions that determine whether a run can be prevented. We first characterize these conditions for an isolated intermediary and then generalize them to the case in which the intermediary can sell assets to prevent runs. The sale of assets can eliminate runs if the intermediary is solvent but illiquid. However, because of cash-in-the-market pricing, this becomes less likely as more intermediaries face problems. In the limit, in case of a general market run, no intermediary can sell assets to forestall a run, and our original solvency and liquidity constraints are again relevant for the stability of financial institutions.
Keywords: E44; E58; G24; 330; Investment banking; securities dealers; repurchase agreements; tri-party repo; runs; financial fragility; Aktienrückkauf; Wertpapierspekulation; Finanzintermediär; Verschuldungsrestriktion; Investmentbank